The effect of different energy sources on growth performance, abdominal fat deposition and fatty liver syndrome in broilers, i. the effect on growth performance and abdominal fat deposition - Şakir Doğan TUNCER; Reşat AŞTI; Behiç COŞKUN; Mehmet Ali TEKEŞ; Hüdaverdi ERER (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the effects of different energy sources used in broiler diets on the growth performance and the albdominal fat deposition. Four hundred male and 400 female day- old Arbro -7 chicks were randomly distributed by sex into sixteen pens, each pen containing 50 chicks. In eght experimental rations, 1. Corn (M); 2. Sunflower oil (2.5 %) (AY1); 3. Sunflower (5%) (AY2); 4. Fish oil (2.5 %) (BY1); 5. Fish oil (5%) (BY2); 6. Animal fat (2.5 %) (HY1); 7. Animal fat (5 %) (HY2); 8. Wheat + Sunflower oil (3 %) (BAY) were used as supplemental or based energy sources. Each ration was fed to one male and one female group. Thus, sixteen groups were set up and the experiment was ended at the 56th day. Mean live weight values of the males were between 1892.93 and 2375.00 grams. The groups of M and BAY had the lowest live weight. the highest values were obtained from the chickens in AYı (2355.58 g), AY2 (2375.00 g) and BY1 (2346.16 g) (P<0.01). There were no significant differences among the live weights of females fed sunflower oil, fish oil and animal fat (P > 0.05). The total feed consumption and feed convertion of male chickens w ere 4.424-5.376 kg and 2.135-2.450 kg, respectively, during the entire experiment. The satisfactory feed convertion values were found in AY2 and BAY. Feed convertion of female chicken groups was in the range of 2.352- 2.574 kg and the chickens in the group fed corn as an energy source consumed more feed for 1 kg weight gain than the other groups. Abdominal fat contents of the males were in the range of 24.1-44.9 g and percent abdominal fat of live weight was in the range of 1.0-2.0 %. Both abdominal fat weight and the percent abdominal fat of live weight were the largest in the groups fed fish oil. In the females, the highest values were obtained in BAY, HY1 and HY2 (55.7, 48.7 and 52.4 g respectively). The percent abdominal fat of li ve weight in the same sex groups was between 1.8 and 2.9 %. According to these results, it is said that the abdominal fat deposition of female chickens was more than the values of males. As a result, because of best effect on increasing growth performanc~ obtained with supplementing various levels of sunflower oil, it is suggested that the vegetable oil be used in broiler rations as an energy subsitute for some part of corn:. On the contrary, fish oil used in broiler rations increased abdominal fat accumulation and caused fishy smell in me at.